Integrity in and Beyond Contemporary Higher Education: What Does it Mean to University Students? - Wong, Sarah Shi Hui; Lim, Stephen Wee Hun; Quinlan, Kathleen M. (Frontiers in Psychology, 2016)
Research has focused on academic integrity in terms of students’ conduct in relation to university rules and procedures, whereas fewer studies examine student integrity more broadly. Of particular interest is whether students in higher education today conceptualize integrity as comprising such broader attributes as personal and social responsibility. We collected and analyzed qualitative responses from 127 students at the National University of Singapore to understand how they define integrity in their lives as students, and how they envisage integrity would be demonstrated in their lives after university. Consistent with the current literature, our data showed that integrity was predominantly taken as “not plagiarizing (in school)/giving appropriate credit when credit is due (in the workplace)”, “not cheating”, and “completing tasks independently”. The survey, though, also revealed further perceptions such as, in a university context, “not manipulating data (e.g., scientific integrity)”, “being honest with others”, “group work commitments”, “conscience/moral ethics/holding true to one’s beliefs”, “being honest with oneself”, “upholding a strong work ethic”, “going against conventions”, and “reporting others”, as well as, in a workplace context, “power and responsibility and its implications”, “professionalism”, and “representing or being loyal to an organization”. The findings suggest that some students see the notion of integrity extending beyond good academic conduct. It is worthwhile to (re)think more broadly what (else) integrity means, discover the gaps in our students’ understanding of integrity, and consider how best we can teach integrity to prepare students for future challenges to integrity and ethical dilemmas.